Safety analysis for grounding potential rise of two neighbouring substations: Case study of metropolitan electricity Authority's system - Phayomhom A. (2017)
This paper presents construction procedures for small air insulated substation (temporary substation) in the existing substation compound to be operated during renovation of the existing air insulated substation (AIS) to be gas insulated substation (GIS). During the time of isolating ground grid of two distribution substations, the effect of the auxiliary grounding system (de-energized electrical power site) of the existing AIS substation will exist. This creates ground potential rise (GPR) to be steep between the ground grids of two neighbouring substations. It is found that the percentage of GPR ratio between the disconnecting auxiliary grounding system and the main ground grid in uniform or homogenous soil is constant while the percentage of GPR ratio are different in case of two-layer soils, i.e. The GPR ratio is proportional to the bottom soil resistivity while it is invertly proportional to the upper soil's. This implies that only a risky case can be considered in substation design, although the condition of soil varies by season (rainy, winter or summer). The ground grid design for the Pathumwan (PM) substation of Metropolitan Electricity Authority (MEA) is examined with the main objective to assess its grounding grid system condition in terms of ground potential rise, maximum touch voltage and step voltage. These three parameters are analyzed to ensure that they satisfy the safety criteria defined in the IEEE Std 80-2000 with five scenarios classified by 25 kA in MEA Distribution System Improvement and Expansion Plan (years 2012-2016). It is found that safety criteria should not be ignored in the meantime of ground grid isolation because the auxiliary grounding system of the existing substation can create steep ground potential rise and therefore the voltage difference can harm personels working nearby and cause damage to equipment in the vicinity of faults, particularly when the ground grid of the two neighbouring substations are not connected. Modelling and simulation are carried out on the Current Distribution Electromagnetic interference Grounding and Soil structure (CDEGS) program.